Biogenic synthesis of mono dispersed Co/CoO nanoparticles using Syzygium cumini leaves for catalytic application. Issue 6 (3rd June 2021) - Din, Muhammad Imran; Rizwan, Rimsha; Hussain, Zaib; Khalid, Rida
Abstract: Copper and copper oxide nanoparticles (Co/CoO NPs) were synthesized by a green approach using Syzygium cumini leaf extract. The formation of synthesized Co/CoO NPs was monitored by using UV–Visible spectroscopy which shows surface plasmon resonance (SPR) at 380 nm. The parameters affecting the particle size or yield of Co/CoO NPs including pH, temperature, reaction time, and concentration of salt also has been studied. The performance or efficiency of catalysts has been investigated by the degradation of 4-nitrophenol (4-NP) and methylene blue (MB) in the presence of sodium borohydride. The kinetic studies displayed that Co/CoO NPs obeyed pseudo-first-order for catalysis of selected contaminants.